Solar governance for the transborder agglomeration of the Greater Geneva based on the solar cadaster development - Desthieux, Gilles; Thebault, Martin (Frontiers in Built Environment, 2024)
As cities are major energy consumers challenges arise in densely populated areas that limit solar resources, hindering the deployment of urban solar power plants. To address this, the paper underscores the importance of digital tools for modeling solar energy accessibility within the urban fabric, focusing on rooftops, building facades, and other relevant locations. In this context, the development of the solar cadaster in Greater Geneva is presented in the paper within the framework of the European INTERREG G2 Solar project (2019-2022). The solar cadaster relies on a rich database from the Geneva Land Information System (SITG), offering comprehensive data on Digital Surface Models, building and roof cadasters, land cover, and more. Notably, this data, including the solar cadaster outputs, is accessible to the public as open data, fostering its extensive use in academia for teaching and research. It serves as a living laboratory for urban solar studies, with its open data approach contributing to widespread adoption. The project, a collaborative effort involving academia, energy utilities, and public institutions on both sides of the border, aims to unite stakeholders and foster a dialogue on solar energy in the region, in line with its commitment to addressing climate change, striving for carbon neutrality by 2050. The paper articulates the steps, methods, and outcomes of the project, offering insights into the challenges of implementing a shared online application tool in a cross-border territory. The propositions are based on feedbacks from stakeholders and lessons learned from case studies. The paper also delves into the shift in the business model for solar PV installations, emphasizing the need to model self-consumption in buildings. It concludes by highlighting the solar cadaster as a unifying means, fostering cohesion among diverse stakeholders in the region's energy sector and propelling them toward common governance around solar energy.